(3GdefgGL aj TQM UMjM eSde Hf GdMLGLs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s ((3CHh HcQ CMeO Hf CHj GdbGSe s)
(3ChdgG (B:s
(3jHOC HHGH GdEaQGO hGdbQBf ef cJGH GdML s
(3BNQgG (B:s
(3jfJgi HHGH cQGgI GdWQhb ef cJGH GdEeGQI Hbhdg (B: (3aCeQge HGdUHQ Edi BNQ GdfgGQ djHdZ NHQ bOhege hjJCgH GdfSGA hZjQgf hGddg CYde s
(3GdfSNI HgG MhGTs
(3ef JMHjS CHj GdYHGS GdefUhQ HGddg Ydi LGeY GdbQhjjf YGe (B1009(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
Keywords: (3GdMOjK h GdeUWdMs